Verifying and assessing the reliability of the learning module of positive design and innovative technology in the integration approach of spiritual knowledge - Zaipah, Ismail; Aede Hatib, Musta’amal @ Jamal; Nornazira, Suhairom; Rohana, Hamzah (Semarak Ilmu Publishing, 2024)
This study was carried out to determine the validity and reliability of the learning module known as The Learning Module of Positive Design and Innovative Technology in The Integration Approach of Spiritual Knowledge (PRBTIFIIS). The PRBTIFIIS module has been built to develop the positive innovative thinking of Form 2 students through a knowledge integration approach with the application of the value of trust and obedience to God, human responsibility as a servant and caliph. The PRBTIFIIS module is built based on the Sidek Module construction model that uses the basic theory of Reverse Maslow's Theory, and Sidek's Learning Theory. A level of validation of the module content was carried out by five experts in the studied field. The content validity of the PRBTIFIIS Module is calculated using the Tuckmen and Waheed Level of Mastery Validity formula. The data obtained is 98.7%. The reliability of the module was obtained from 16 second-grade students who participated in the implementation of the pilot study. The Cronbach's Alpha score obtained for the reliability of the module was 0.97. The findings of the study show that the developed PRBTIFIIS Module has high validity and reliability and the PRBTIFIIS module is available to test its effectiveness.